Advances in the Signaling Pathways Downstream of Glial-Scar Axon Growth Inhibitors - Sami, Armin; Selzer, Michael E.; Li, Shuxin (Frontiers in Cellular Neuroscience, 2020)
Axon growth inhibitors generated by reactive glial scars play an important role in failure of axon regeneration after CNS injury in mature mammals. Among the inhibitory factors, chondroitin sulfate proteoglycans (CSPGs) are potent suppressors of axon regeneration and are important molecular targets for designing effective therapies for traumatic brain injury or spinal cord injury (SCI). CSPGs bind with high affinity to several transmembrane receptors, including two members of the leukocyte common antigen related (LAR) subfamily of receptor protein tyrosine phosphatases (RPTPs). Recent studies demonstrate that multiple intracellular signaling pathways downstream of these two RPTPs mediate the growth-inhibitory actions of CSPGs. A better understanding of these signaling pathways may facilitate development of new and effective therapies for CNS disorders characterized by axonal disconnections. This review will focus on recent advances in the downstream signaling pathways of scar-mediated inhibition and their potential as the molecular targets for CNS repair.